Exploring the Activity of Daily Living of Sexual Activity: A Survey in Occupational Therapy Education - Helene L. Lohman; Alexandra Kobrin (Scholarworks @ WMU, 2017)
This study aimed to query occupational therapy educators in professional programs in the United States about the amount of time spent addressing sexual activity and the type and depth of education related to sexual activity. The study aims to inform educators about how sexual activity is taught. A cross-sectional survey research design was used with both closed- and open-ended questions. A total of 51 educators participated. An average of 3.5 hr was spent teaching sexual activity. Many of the participants were comfortable teaching sexual activity. However, some reported that sexual activity was often an overlooked topic in occupational therapy curriculum and was not emphasized as much as other activities of daily living. In addition, participants reported that the under emphasis of teaching sexuality may be due to a lack of educational background, the broadness of the topic, discomfort of the students, and a lack of information in textbooks. Most of the participants are comfortable teaching sexual activity and believe that it is an important topic in occupational therapy curriculum. However, many consider it an overlooked topic specifically with chronic conditions and sexually transmitted infections. Therefore, educating instructors on sexual activity and pedagogical methods will enhance occupational therapy curriculum.